METHOD DEVELOPMENT AND FORCE DEGRADATION STUDIES FOR SIMULTANEOUS ESTIMATION OF SALBUTAMOL SULFATE, ETOFYLLINE AND BROMHEXINE HYDROCHLORIDE IN PHARMACEUTICAL DOSAGE FORM USING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD - Rao, Nutan; Gawde, Kajal D (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study describes the stability indicating reversed-phase high-performance liquid chromatography (RP-HPLC) method for simultaneous estimation of salbutamol sulfate (SAL), etofylline (ETO), and bromhexine hydrochloride (BROM) in pharmaceutical dosage forms. Methods: The proposed RP-HPLC method was developed using Shimadzu prominence-i LC-2030 HPLC system equipped with ultraviolet (UV) detector and chromatographic separation was achieved isocratically using Shim-pack C18 (250 mm×4.6mm, 5 μ) column at a flow rate of 1 ml/min and the run time was 13 min. The mobile phase consisted of acetonitrile: 0.1M potassium dihydrogen phosphate buffer (35:65) with pH adjusted to 3.0 and eluents were scanned using UV detector at 225 nm. Result: The retention time of SAL, ETO, and BROM was found to be 2.319 min, 2.698 min, and 10.329 min, respectively. The calibration curve was linear over the concentration ranges of 1.6–3.2 μg/ml, 160–320 μg/ml, and 6.4–12.8 μg/ml for SAL, ETO, and BROM, respectively. Conclusion: The stability indicating method was developed by subjecting the drugs to stress conditions such as acid and base hydrolysis, oxidation, humidity, and photo- and thermal degradation and the degraded products formed were resolved successfully from the samples. Therefore, the proposed method can be used as a more convenient and efficient option for the simultaneous estimation of all the three drugs in bulk and combined